DIFFERENCES IN MECHANICAL EFFICIENCY BETWEEN FEMALE AND MALE FOOTBALL PLAYERS DURING OFFICIAL MATCHES (Kinesiology, 2025)
This study aimed to compare the values of external load measures and mechanical efficiency between male and female soccer players considering the match periods. A male professional soccer team (n=19) and a female professional soccer team (n=16) were monitored in official matches by Global Positioning System (GPS) devices (male 137 and female 144 observations). The external load variables studied were distance covered per minute (DCmin in m∙min-1), player load per minute (PL in AU∙min-1) and the mechanical efficiency obtained through the relationship of PL and DC (PLm in AU∙m-1) over 90 minutes of official match divided into six periods of 15 minutes each. The results show that in all the periods studied, DCmin and PLmin for male soccer players were higher than for female players (ES: high and moderate for DCmin and PLmin, respectively; p 60-75 = 75-90), as well as a decrease (p 30-45 = 60-75 = 75-90, 15-30 > 75-90 & 45-60 > 60-75 = 75-90 for male; and, 0-15 > 30-45 = 60-75 = 75-90 for female). The decrease in values of PLmin and DCmin were not homogeneous, so the decoupling of these values in both genders as the match progresses could be induced by fatigue. Therefore, the findings could have a practical application: coaches and sports scientists could use the mechanical efficiency indicator to detect fatigue and then apply intervention strategies to improve performance or plan recovery.Key words: external load, GPS, soccer, team sport, gender